Introducing tax education to non-accounting undergraduates : survey evidence from University Technology of MARA, Shah Alam / Anis Barieyah Mat Bahari - Mat Bahari, Anis Barieyah (2007)
In the era of Self Assessment System (SAS), taxpayers are required to assess their tax liability themselves. Thus, tax knowledge is crucial to assist and guide them in assessing their tax accurately. In order to possess tax knowledge, tax education needs to be introduced to all students regardless of disciplines. Thus far, in Malaysia, tax education is only being taught to accounting . and business undergraduates. This study solicits the non-accounting undergraduates' views towards introducing tax education into nonaccounting curriculum. The study aims i) to solicit the feasibility for introducing tax education to non-accounting undergraduates, ii) to assess the level of tax knowledge of non-accounting undergraduates, and iii) to identify the relevant tax topics to be covered for non-accounting curriculum. Questionnaire was used to collect data. In total, 450 questionnaires were distributed to non-accounting undergraduates that pursuing outcampus program in four faculties in University Technology of MARA (UiTM), Shah Alam. One hundred ninety usable questionnaires were collected and used for data analysis. The findings showed that more than half of the respondents did not know that SAShas already been implemented for two years. Nearly 850/0 of the respondents did not know about the Public Rulings issued by the Inland Revenue Board. About 41% of nonaccounting undergraduates possessed low level of tax knowledge in respect of personal taxation. Nearly 72% of the respondents had never learned taxation and about 64% of the respondents expressed their interest in learning taxation at undergraduate levels. Majority (88.4 %) of the respondents perceived that taxation is an important subject and 85.3% of the respondents indicated that learning taxation would help them in computing tax liability correctly. Furthermore, 75% of the respondents perceived that learning tax will enhance tax compliance among taxpayers. Notably, most of the tax topics outlined were favored by the respondents. The tax topics that non-accounting undergraduates would like to learn the most are basic concepts of taxation and tax policies, personal taxation as well as tax planning for individuals. This study provides important insights for top management, academics and the relevant authorities in UiTM towards the need of introducing tax education to non-accounting undergraduates.